CompTIA Linux+ powered by Linux Professional institute study guide exams LX0-103 and exam LX0-104 - Bresnahan, Christine; Blum, Richard (Sybex, 2015)
CompTIA Linux+ Study Guide is your comprehensive study guide for the Linux+ Powered by LPI certification exams. With complete coverage of 100% of the objectives on both exam LX0-103 and exam LX0-104, this study guide provides clear, concise information on all aspects of Linux administration, with a focus on the latest version of the exam. You'll gain the insight of examples drawn from real-world scenarios, with detailed guidance and authoritative coverage of key topics, including GNU and Unix commands, system operation, system administration, system services, security, and more, from a practical perspective that easily translates into on-the-job know-how. You'll also get access to helpful study tools, including bonus practice exams, electronic flashcards, and a searchable glossary of key terms that are important to know for exam day.